Prenatal assessment of cerebellar vermian lobulation: fetal MRI with 3‐Tesla postmortem validation. (8th October 2018) - Dovjak, G. O.; Brugger, P. C.; Gruber, G. M.; Song, J. W.; Weber, M.; Langs, G.; Bettelheim, D.; Prayer, D.; Kasprian, G.
ABSTRACT: Objectives: To optimize the imaging assessment of fetal hindbrain malformations, this observational magnetic resonance imaging (MRI) study aimed to assess whether fetal vermian lobulation can be quantified accurately and whether the relative growth of vermian lobules is uniform. Methods: This retrospective study included singleton fetuses which underwent T2‐weighted MRI in vivo with a 1.5‐Tesla (T) scanner or within 24 h postmortem with a 3‐T scanner between January 2007 and November 2016 at the Medical University of Vienna. We included only those showing normal structural brain development on ultrasound and MRI and which had image quality appropriate for quantitative analysis, i.e. good image quality and a precise midsagittal slice. Fetal brains were segmented and, for all discernible vermian lobules, we determined the mean relative area contribution (MRAC, the proportion of the lobule relative to the total vermian area, in terms of number of voxels). Inter‐ and intrarater measurement variability of a representative selection (21 cases) was determined by intraclass correlation coefficient (ICC) for voxel‐based differences. A linear regression model was used to assess the correlation between the relative size of each vermian lobule (i.e. MRAC) and gestational age. Results: A total of 78 fetuses scanned in vivo aged 18–32 gestational weeks and seven fetuses scanned postmortem aged 16–30 weeks had a precise midsagittal slice and image quality sufficient for quantitative analysis. After 22 weeks of gestation, seven of the nine known vermian lobules could be discriminated reliably. The MRAC showed a mean ± SD difference of only 2.89 ± 3.01% between in‐vivo and postmortem measurements. The ICC of voxel‐based interrater differences was mean ± SD, 0.91 ± 0.05 and the intrarater ICC was 0.95 ± 0.03. Growth of cerebellar lobules was non‐uniform: the MRAC of culmen and DFT (declive + folium + tuber) increased with gestational age, whereas that of lingula, centralis, pyramis and nodulus decreased. The growth of the uvula showed no significant correlation with gestational age. Conclusions: Fetal vermian lobulation can be assessed accurately and reliably after 22 weeks on precise midsagittal sequences with 1.5‐T T2‐weighted MRI. Fetal vermian lobules show non‐uniform growth, with expansion of DFT and culmen at the expense of the other vermian lobules. Evaluation and elucidation of vermian lobulation in normal fetuses should enable better characterization of fetuses with hindbrain malformations. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.